Paraquat Toxicity on Root Nodule Formation on Macroptiliuma tropurpureum Urb. and Its Corelation with Population of Rhizobium sp. - Erni Martani; Sebastian Margino; Medhina Magdalena (Jurnal Perlindungan Tanaman Indonesia, 2004)
This study was designed to investigate the paraquat toxicity toward root nodulation by Rhizobium on Macroptilium atropurpureum as an indicator plant. The legume was grown in Thornton medium treated with several concentrations of paraquat and inoculated with R.japonicum 143 (Rj-143) or Rhizobium sp. C-1.1. These bacteria represent cross-inoculation of soybean and cover-crops legumes, respectively. Nodule formation and Rhizobium population were measured periodically. At the end of planting time, nitrogenase activity of the nodules was analysis based on ARA (Acethylene Reduction Analysis) method. The results showed that nodules in plants inoculated with Rhizobium without addition paraquat, were formed within four weeks. There was no nodulation when paraquat was added. Paraquat was toxic to the plant, causing chlorosis, stunting, drying of the plant tissues, and death. The symptoms were detected at the second week after planting time. Paraquat also decreased Rhizobium population from 10^6 to 10^2 or 10^1 CFU/mL at 40 and 100 pp, respectively. These results depicted that paraquat disturbed the plant before nodulation, and at the same time Rhizobium populatin decreased until below minimal population required for nodulation. Therefore, the process of nodulation was disturbed, and in some treatments there was nodulation. It was concluded that paraquat was toxic to both plant and the Rhizobium, which cause nodulation failure.